MODEL PERUBAHAN SERAPAN MINYAK PADA KENTANG SELAMA PENGGORENGAN - Rina Pratiwi Pudja, Ida Ayu (Universitas Udayana, 2009)
Frying is one of fast and practical mean of cookingprocess of food using fat or oil media. The aims of theresearch were to find out, to test and to apply the model of oilabsorption in potatoes during frying. Frying temperatureswere adjusted at 140oC, 160oC and 180oC, with interval timeof analysis at 0, 30, 90, 150, 300, dan 600 seconds. Freshpotatoes were cut in cylinder shaped with diameter of 0.9 cmand 4 cm long. The result showed that the higher fryingtemperature, the higher absorption of fat during frying. Therate of fat absorption could be analogically expressed as theNewton model for cooling, to predict the absorption of fatduring frying of fresh potatoes in other temperature.